Small extracellular vesicles derived from sequential stimulation of canine adipose-derived mesenchymal stem cells enhance anti-inflammatory activity - Saranyou Oontawee; Parkpoom Siriarchavatana; Watchareewan Rodprasert; Irma Padeta; Yudith Violetta Pamulang; Poorichaya Somparn; Trairak Pisitkun; Boondarika Nambooppha; Nattawooti Sthitmatee; Daneeya Na Nan; Thanaphum Osathanon; Hiroshi Egusa; et al. (BMC Veterinary Research)
Abstract Background Small extracellular vesicles (sEVs) derived from mesenchymal stem cells (MSCs) are recognized for their therapeutic potential in immune modulation and tissue repair, especially in veterinary medicine. This study introduces an innovative sequential stimulation (IVES) technique, involving low-oxygen gas mixture preconditioning using in vitro fertilization gas (IVFG) and direct current electrical stimulation (ES20), to enhance the anti-inflammatory properties of sEVs from canine adipose-derived MSCs (cAD-MSCs). Initial steps involved isolation and comprehensive characterization of cAD-MSCs, including morphology, gene expression, and differentiation potentials, alongside validation of the electrical stimulation protocol. IVFG, ES20, and IVES were applied simultaneously with a control condition. Stimulated cAD-MSCs were evaluated for morphological changes, cell viability, and gene expressions. Conditioned media were collected and purified for sEV isolation on Day1, Day2, and Day3. To validate the efficacy of IVES for sEV production, various analyses were conducted, including microscopic examination, surface marker assessment, zeta-potential measurement, protein quantification, nanoparticle tracking analysis, and determination of anti-inflammatory activity. Results We found that IVES demonstrated non-cytotoxicity and induced crucial genotypic changes associated with sEV production in cAD-MSCs. Interestingly, IVFG influenced cellular adaptation, while ES20 induced hypoxia activation. By merging these stimulations, IVES enhanced sEV stability and quality profiles. The cAD-MSC-derived sEVs exhibited anti-inflammatory activity in lipopolysaccharide-induced RAW264.7 macrophages, emphasizing their improved effectiveness without cytotoxicity or immunogenicity. These effects were consistent across day 3 collection, indicating the establishment of an effective protocol for sEV production. Conclusions This research established an innovative sequential stimulation method with positive impact on sEV characteristics including stability, quality, and anti-inflammatory activity. This study not only contributes to the enhancement of sEV production but also sheds light on their functional aspects for therapeutic interventions.